1-(2-pyridylazo) 2-naphthol-modified bacterial cellulose/multiwall carbon nanotube/silicon dioxide membrane for selectively adsorbed Er (III). Issue 3 (4th March 2023) - Zhang, Yuzhe; Hua, Jie; Zhao, Meiwen; Wu, Hao; Shao, Yizi; Zhou, Man; Gu, Peiyang; Li, Zhongyu
Abstract: Considering the economic benefits and environmental pollution, it is of great significance to recover rare earth elements from wastewater. In this article, the modified bacterial cellulose is the raw material, and multi-wall carbon nanotubes are added to construct together. The ion imprinting technology is introduced to prepare a silicon-based modified film for the recovery of Er(III) and selectively adsorption function of Er(III) in experiments. The maximum adsorption amount of modified carbon nanotube silicon bacterial cellulose composite imprinted membrane can reach 46.52 mg L −1, and the adsorption capacity is greatly improved compared to other methods that of the non-imprinted membrane. The adsorption efficiency of Er(III) can reach 92%.